1999
DOI: 10.1063/1.371195
|View full text |Cite
|
Sign up to set email alerts
|

Excess silicon at the silicon nitride/thermal oxide interface in oxide–nitride–oxide structures

Abstract: The chemical composition and structure of Si 3 N 4 /thermal ͑native and wet͒ SiO 2 interface in oxidenitride-oxide structures are studied by using secondary ion mass spectroscopy, electron energy loss spectroscopy ͑EELS͒ and Auger electron spectroscopy ͑AES͒ measurements. EELS and AES experiments show the existence of excess silicon at the Si 3 N 4 /thermal SiO 2 interface. Excess silicon ͑Si-Si bonds͒ at Si 3 N 4 /SiO 2 interface exists in the form of Si-rich silicon oxynitride. Numerical simulation of the Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 32 publications
0
42
0
Order By: Relevance
“…19,25 In the following, we propose a mechanism for the unexpected broadening of the EBISA deposits on the membrane: In a first step, electrons are ejected upon high energy electron irradiation, mainly due to SE emission. In a second step, the resulting holes accumulate at the SiO 2 /Si 3 N 4 interface, which is a Si-enriched silicon oxynitride with a thickness of $0.6-0.8 nm, 26,27 and which is well known to trap charges. [26][27][28][29] Due to the Si enrichment, the interface should be more conductive than the SiO 2 or the Si 3 N 4 layer.…”
Section: -mentioning
confidence: 99%
See 1 more Smart Citation
“…19,25 In the following, we propose a mechanism for the unexpected broadening of the EBISA deposits on the membrane: In a first step, electrons are ejected upon high energy electron irradiation, mainly due to SE emission. In a second step, the resulting holes accumulate at the SiO 2 /Si 3 N 4 interface, which is a Si-enriched silicon oxynitride with a thickness of $0.6-0.8 nm, 26,27 and which is well known to trap charges. [26][27][28][29] Due to the Si enrichment, the interface should be more conductive than the SiO 2 or the Si 3 N 4 layer.…”
Section: -mentioning
confidence: 99%
“…In a second step, the resulting holes accumulate at the SiO 2 /Si 3 N 4 interface, which is a Si-enriched silicon oxynitride with a thickness of $0.6-0.8 nm, 26,27 and which is well known to trap charges. [26][27][28][29] Due to the Si enrichment, the interface should be more conductive than the SiO 2 or the Si 3 N 4 layer. Therefore, a radial transport of the holes along this Si-enriched interface occurs, even to areas beyond BSE emission.…”
Section: -mentioning
confidence: 99%
“…The hole capturing on a Si-Si bond plays an important role in silicon devices with oxynitride as the gate dielectric [36]. Si-Si bonds were observed experimentally at the Si 3 N 4 / termal oxide interface [21]. Excess hole and electron capturings at the interface were also found [37,38].…”
Section: Va Gritsenko Yun Novikov Av Shaposhnikov Hei Wong mentioning
confidence: 97%
“…In addition, if the distance between two defects is about 3.1Å, other mechanisms for the carrier localization are also possible. It was suggested that the electron and hole capturing could also occur at a neutral diamagnetic ≡ Si−Si ≡ defect [2,4,10,20,21]. The validity of these two models for Si 3 N 4 is still under discussion.…”
Section: (Received 30 January 2003)mentioning
confidence: 99%
“…µÏÇÐßÛÇÐËÇ ÕÑÎÜËÐÞ ÑÕ 8 AEÑ 2 ÐÏ ÔÑÒÓÑÄÑÉAEÂÇÕÔâ ÖÄÇÎËÚÇÐËÇÏ ÒÑÍÂÊÂÕÇÎâ ÒÓÇÎÑÏÎÇÐËâ ÑÕ 1,52 AEÑ 2,0. ±ÑAEÑÃÐÞÌ à××ÇÍÕ ÐÂÃÎá-AEÂÎÔâ ÓÂÐÇÇ ¤ÑÐÑÐÑÏ Ô ÔÑÂÄÕÑÓÂÏË [13].¯Â ÓËÔÖÐÍÇ 2 6 ÊÄÇÐßÇÄ, n 1,57 [18,19] ²ËÔ. 14.…”
mentioning
confidence: 99%